A delayed swelling gel particle profile control system, a preparation method and application thereof
Patent Information
- Application Number
- CN202611436511.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]本发明是为了解决现有技术中存在的凝胶颗粒调驱体系遇水后溶胀速度过快,易造成近井地带堵塞、调驱波及范围有限、采收率提升不足等问题而提出的,其目的是提供一种缓膨胀性凝胶颗粒调驱体系及其制备方法与应用
本发明提供了一种缓膨胀性凝胶颗粒调驱体系及其制备方法与应用,通过设计新型海藻酸钠-壳聚糖复合包覆材料对现有核心凝胶颗粒进行均匀包覆,形成“核心-包覆层”的核壳结构,实现对凝胶颗粒溶胀速率的精准调控,同时兼顾调驱体系的封堵强度、耐温抗盐性和运移性能,解决近井堵塞、调驱波及范围有限的问题,提升油藏采收率10%~15%,延长调驱有效期至15个月~20个月,适用于高中低渗(渗透率50mD~2000mD)、高温高盐(温度50℃~130℃,矿化度3000mg/L~55000mg/L)及非均质油藏(渗透率变异系数0.5~1.2)的调驱开采;经实验验证,本发明凝胶颗粒溶胀速率降低60%~92%(现有未包覆凝胶颗粒12h~24h内达到最大膨胀率,本发明缓膨胀性凝胶颗粒60h~108h内达到最大膨胀率),最终膨胀倍率保持8倍~35倍,封堵率可达86%~95%;本发明缓膨胀性凝胶颗粒在50℃~130℃、矿化度3000mg/L~55000mg/L环境下静置72h,膨胀率保留率≥88%;本发明制备工艺简单、成本可控(较现有体系降低10%~18%)、环保无储层伤害,能有效解决现有调驱颗粒体系遇水膨胀快,造成近井堵塞、调驱波及范围有限的问题,采收率提升10%~15%,适用于高中低渗、高温高盐及非均质油藏,应用前景广泛。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical flooding technology in petroleum extraction, specifically relating to a slow-expansion gel particle flooding system, its preparation method, and its application. Background Technology
[0002] After oil extraction enters the medium-to-high water-cut development stage, chemical flooding technology is one of the core means to improve reservoir heterogeneity and enhance remaining oil recovery. Among them, gel particle flooding systems are widely used in flooding operations of various reservoirs due to their good mobility control, plugging performance, and adaptability. Existing gel particle flooding systems are mostly prepared using acrylamide polymers as the main raw material, supplemented by crosslinking agents, stabilizers, etc., but this type of system has key technical defects: 1) The swelling rate is too fast after contact with water, usually reaching the maximum expansion volume within a few hours after contact with formation water; 2) In offshore oilfields, the particle stability is affected by the near-wellbore shear of the screen pipe.
[0003] This excessively rapid swelling rate can cause gel particles to swell significantly before migrating to high-permeability channels or deep oil-rich areas within the reservoir during injection. This can clog pore throats in the near-wellbore zone, leading to a sharp increase in injection pressure (in some blocks, the injection pressure can rise to over 90% of the reservoir fracture pressure), affecting the effective injection of the modulator. Simultaneously, rapid swelling also increases the brittleness of the gel particles, making them prone to breakage during reservoir migration (breakage rate can reach 30%–40%). This reduces the stability of the plugging process and the duration of the modulator's effectiveness (typically only 6–12 months), failing to effectively drive the remaining oil in the deep reservoir. Ultimately, this results in poor modulator performance and limited recovery (generally only 5%–8%).
[0004] Currently, to address the issue of excessively rapid swelling of gel particles, existing technologies mostly aim to achieve slow swelling by adjusting the degree of cross-linking within the gel particles. However, this approach significantly reduces the final swelling ratio of the gel particles (down to 5-8 times) and the plugging strength (plugging rate below 70%), failing to balance the slow swelling effect with the plugging performance. Some technologies attempt to use simple surface adsorption modification, but the modified layer does not bond firmly with the gel particles and is prone to detachment in high-temperature, high-salt reservoir environments (detachment rate can reach 25%-35% in 72 hours), making it difficult to sustain the slow swelling effect.
[0005] Therefore, developing a slow-expansion gel particle regulation and drive system that can stably coat gel particles, effectively reduce the swelling rate, and does not affect the final expansion performance and sealing effect of gel particles has become an urgent technical need to be addressed in the current oil extraction field. Summary of the Invention
[0006] This invention addresses the problems in existing technologies, such as excessively rapid swelling of gel particle-based controlled-drive systems upon contact with water, which can easily lead to blockage in the near-wellbore zone, limited controlled-drive coverage, and insufficient recovery rate enhancement. The aim is to provide a slow-expanding gel particle-based controlled-drive system, its preparation method, and its application.
[0007] This invention is achieved through the following technical solution: A slow-expansion gel particle modulating system, wherein the modulating system comprises the following components and the mass percentage of each component: Slow-expanding gel particles: 0.1%~0.5%; Corrosion inhibitor 0.05%~0.8%; The system simulates the remaining formation water; The components and their mass percentages in the slow-expanding gel particles are as follows: Core gel particles: 55%~85%; Composite coating material 4%~18%; Dispersant 1%~6%; Organic boron crosslinking agent 0.3%~2.5%; Particles simulate the remaining formation water.
[0008] In the above technical solution, the core gel particles are acrylamide-based gel particles; the components of the acrylamide-based gel particles are partially hydrolyzed polyacrylamide (HPAM, molecular weight 8 million to 20 million), N,N'-methylenebisacrylamide (crosslinking agent) and urea (stabilizer), with a mass ratio of 100:(0.3~2.5):(0.8~3.5); the particle size of the core gel particles is 50nm~200nm, and the expansion ratio is 8 times to 35 times, ensuring that the core gel particles have good sealing performance and aging resistance (shelf life ≥12 months at room temperature).
[0009] In the above technical solution, the composite coating material is a slow-expanding core component; the composite coating material includes sodium alginate and chitosan, with a mass ratio of sodium alginate to chitosan of (1.8~3.2):1; the viscosity of sodium alginate is 100mPa·s~300mPa·s; the degree of deacetylation of chitosan is ≥85%; the coating layer formed by the combination of sodium alginate and chitosan has slow hydrolysis characteristics (hydrolysis rate 0.02g / h~0.05g / h), which can effectively slow down the water penetration rate (penetration rate reduced by 60%~75%), and is firmly bonded to the core gel particles (72h detachment rate ≤5%), avoiding detachment in the oil reservoir environment.
[0010] In the above technical solution, the dispersant is a polyether-modified silane coupling agent with a molecular weight of 800~2200; the surface tension of the polyether-modified silane with a molecular weight of 800~2200 is ≤35mN / m, which has both dispersing and interfacial activity, can prevent particle agglomeration (agglomeration rate ≤8%), improve the tightness of the bonding between the coating layer and the core gel particles, and enhance the compatibility of the system with the reservoir rock (contact angle ≤45°).
[0011] In the above technical solution, the organoboron crosslinking agent is at least one of trimethyl borate, triethyl borate, or sodium borohydride; the crosslinking time of the crosslinking agent is 30 min to 60 min, which is used to promote the crosslinking reaction of the composite coating material and form a dense and stable coating layer (porosity ≤ 3%).
[0012] In the above technical solution, the corrosion inhibitor is an imidazoline corrosion inhibitor; the imidazoline corrosion inhibitor is at least one of alkyl imidazoline corrosion inhibitor (Wuhan Organic Industry Co., Ltd. WY-01), amide imidazoline corrosion inhibitor (Jiangsu Haian Petrochemical Plant HS-101), or phosphate imidazoline corrosion inhibitor (Nanjing Gutian Chemical Co., Ltd. GT-200); the corrosion inhibitor has a corrosion inhibition rate ≥90%, inhibiting the corrosion of the injection-production well tubing (N80 steel) and reservoir rock by the modulating drive system (corrosion rate ≤0.05mm / a).
[0013] In the above technical solution, the simulated formation water and the particle-based simulated formation water are simulated formation water with completely identical compositions. The salinity of the simulated formation water is 3000 mg / L to 55000 mg / L, and the Na content in the simulated formation water is [missing information]. + Concentrations of 1000 mg / L to 30000 mg / L, Ca 2+ Concentrations of 100 mg / L to 2000 mg / L, Mg 2+ The concentration ranges from 100 mg / L to 2000 mg / L, suitable for different types of reservoir formation environments.
[0014] A method for preparing the aforementioned slow-expansion gel particle modulating system includes the following steps: S1. Pretreatment of core gel particles: Place the core gel particles in a vacuum drying oven and dry them at 75℃~105℃ for 1.5h~4.5h to remove surface moisture (moisture content reduced to ≤0.5%), then cool to room temperature for later use. S2. Preparation of the composite coating solution: Sodium alginate and chitosan were added to the granular simulated formation water and placed in a constant temperature water bath at 35℃~65℃. The mixture was stirred at a speed of 1200r / min~2200r / min for 25min~65min until completely dissolved. Then, an organoboron crosslinking agent and a dispersant were added, and the mixture was stirred for another 15min~35min. The pH of the reaction system was adjusted to 6.0~8.0 to prepare a composite coating solution. S3, Coating reaction: The core gel particles pretreated in step S1 are slowly added to the composite coating liquid, and the stirring speed is controlled at 400 r / min to 900 r / min. The reaction is carried out at a constant temperature of 35℃ to 65℃ for 0.8h to 2.5h, so that the composite coating material is uniformly attached to the surface of the core gel particles to form slow-expanding gel particles with a core-shell structure. S4. Curing and Drying: The mixture obtained in step S3 is placed in a constant temperature drying oven at 55℃~85℃ for 3.5h~6.5h to fully cure the coating layer (hardness ≥0.8MPa). Particles with a particle size of 70nm~240nm are screened out by sieving to ensure the uniformity of the driving system (particle size distribution range ≤500nm). S5, System Combination: The slow-expansion gel particles with a particle size of 70nm~240nm selected in step S4 and the corrosion inhibitor were added to the system to simulate formation water. The mixture was stirred with a low-speed stirrer at a speed of 250r / min~550r / min for 8min~25min to prepare a uniform and stable slow-expansion gel particle regulation and driving system (the standard for uniformity and stability is: no stratification or precipitation after standing for 72h).
[0015] In the above technical solution, the stirring process in step S2 is supplemented by ultrasonic dispersion with a power of 150W~550W and a dispersion time of 10min~20min to improve the uniformity of the coating liquid (particle size distribution variation coefficient ≤0.15).
[0016] In the above technical solution, during the isothermal reaction in step S3, the particle size change is monitored in real time by a laser particle size analyzer, and the data is recorded every 10 minutes to ensure that the coating layer thickness is uniform (20nm~40nm).
[0017] The aforementioned slow-expansion gel particle modulating and driving system is applied in the modulating and driving development of high, medium and low permeability reservoirs, high temperature and high salinity reservoirs and heterogeneous reservoirs; the permeability of the high, medium and low permeability reservoirs is 50mD~2000mD; the temperature of the high temperature and high salinity reservoirs is 50℃~130℃ and the salinity is 3000mg / L~55000mg / L; the coefficient of variation of permeability of the heterogeneous reservoirs is 0.5~1.2.
[0018] The beneficial effects of this invention are: This invention provides a slow-expansion gel particle-based controlled-flood system, its preparation method, and its application. By designing a novel sodium alginate-chitosan composite coating material to uniformly coat existing core gel particles, a core-shell structure of "core-coating layer" is formed. This allows for precise control of the gel particle swelling rate while simultaneously considering the system's plugging strength, temperature and salt resistance, and migration performance. It solves the problems of near-wellbore blockage and limited controlled-flood sweep range, increasing reservoir recovery by 10%–15% and extending the effective period of controlled-flooding to 15–20 months. It is suitable for controlled-flooding in high, medium, and low permeability reservoirs (permeability 50 mD–2000 mD), high-temperature and high-salinity reservoirs (temperature 50℃–130℃, salinity 3000 mg / L–55000 mg / L), and heterogeneous reservoirs (permeability variation coefficient 0.5–1.2). Experimental verification shows that this invention... The swelling rate of the gel particles is reduced by 60%~92% (existing uncoated gel particles reach their maximum swelling rate within 12h~24h, while the slow-swelling gel particles of this invention reach their maximum swelling rate within 60h~108h), and the final swelling ratio remains at 8 times~35 times, with a plugging rate of 86%~95%. The slow-swelling gel particles of this invention retain an expansion rate of ≥88% after standing for 72h at 50℃~130℃ and a salinity of 3000mg / L~55000mg / L. The preparation process of this invention is simple, cost-controllable (10%~18% lower than existing systems), environmentally friendly and without reservoir damage. It can effectively solve the problems of rapid expansion upon contact with water in existing modulating and driving particle systems, which cause near-wellbore blockage and limited modulating and driving sweep range. The recovery rate is increased by 10%~15%. It is suitable for high, medium and low permeability, high temperature and high salinity and heterogeneous reservoirs, and has a wide range of applications. Attached Figure Description
[0019] Figure 1 This is a graph showing the initial particle size and the particle size after swelling for different times in Example 1 of the present invention for the slow-swelling gel particles; Figure 2 This is a pressure curve diagram of the displacement process between the slow-expanding gel particles and the uncoated gel particles in Embodiment 1 of the present invention; Figure 3 This is a graph showing the injection pressure, water content, and recovery rate curves of the slow-expansion gel particle regulation system in Example 3 of the present invention during the regulation experiment.
[0020] For those skilled in the art, other related figures can be obtained from the above figures without any creative effort. Detailed Implementation
[0021] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0022] Unless otherwise specified, all raw materials used in this invention are commercially available products.
[0023] The performance of the slow-expansion gel particle modulated displacement system prepared in the examples was tested, including: I. Swelling rate test: The test method is as follows: Take 5.000g of the slow-expanding gel particles (the slow-expanding gel particles obtained in step S4) and uncoated gel particles (obtained by processing only in steps S1 and S4 of the present invention) prepared in any embodiment, put them into 500mL of simulated formation water, stir evenly, measure the initial particle size of the slow-expanding gel particles and uncoated gel particles with a laser particle size analyzer, then seal and store them in a constant temperature water bath at a set temperature (50℃~130℃). Every 1h, measure the median particle size D50 of the slow-expanding gel particles and uncoated gel particles with a laser particle size analyzer, calculate the expansion rate at different times, and plot the expansion rate-time curve. Each group of experiments is repeated 3 times, and the average value is taken. The formula for calculating the expansion ratio is:
[0024] II. Coating layer stability test: The test method is as follows: The slow-expansion gel particles prepared in any embodiment (the slow-expansion gel particles obtained in step S4) are placed in simulated formation water and left to stand for 720 hours at 50℃~130℃. The median particle size is measured with a laser particle size analyzer, the change in particle expansion rate is determined, and the coating layer shedding rate is calculated by differential gravity method. The formula for calculating the retention rate is:
[0025] The formula for calculating the 720h expansion rate is the same as the formula for calculating the "expansion rate" in the above swelling rate test. The maximum expansion rate is the value corresponding to the expansion rate reaching its maximum in the expansion rate-time curve plotted during the swelling rate test.
[0026] The formula for calculating the shedding rate is:
[0027] III. Blocking Performance Test: The test method is as follows: Using artificial cores with a permeability of 50mD~2000mD, after pretreatment with saturated simulated formation water, the controlled-drive system prepared by any embodiment with a flow rate of 0.5mL / min (the controlled-drive system obtained after preparation in step S5) is injected. The valves at both ends of the core holder are closed and the core is left to stand for 48h. Then, simulated formation water is injected at the same flow rate, and the pressure changes under different injection volumes are recorded. The plugging rate and breakthrough pressure are calculated. The formula for calculating the blocking rate is:
[0028] IV. Oil displacement effect test: The test method is as follows: A high-temperature and high-pressure displacement device is used to simulate the reservoir temperature (50℃~130℃). Water flooding is first performed at a flow rate of 1.0 mL / min until the water cut reaches 98%, and the water flooding recovery rate is recorded. Then, the modified displacement system prepared by any embodiment (the modified displacement system obtained after step S5) is injected at the same flow rate at 0.3~1.0 times the pore volume. The device is closed and allowed to stand for 24~48 h. Water flooding is then performed again until the water cut reaches 98%, and the total oil production is recorded. The total recovery rate is calculated. Each experiment is repeated in triplicate, and the average value is taken.
[0029] Example 1
[0030] A slow-expansion gel particle modulating system, wherein the modulating system comprises the following components and the mass percentage of each component: Slow-expanding gel particles: 0.2%; Alkyl imidazoline corrosion inhibitor 0.3%; The system simulates the remaining formation water; The components and their mass percentages in the slow-expanding gel particles are as follows: Core gel particles account for 70%; Composite coating material 10%; Dispersant 3%; 1% organic boron crosslinking agent; Particles simulate the remaining formation water.
[0031] The core gel particles contain partially hydrolyzed polyacrylamide, N,N'-methylenebisacrylamide, and urea in a mass ratio of 100:1:2. The partially hydrolyzed polyacrylamide has a molecular weight of 12 million, and the core gel particles have a particle size of 100nm~150nm. The composite coating material is composed of sodium alginate and chitosan in a mass ratio of 2:1, wherein the viscosity of sodium alginate is 200 mPa·s and the degree of deacetylation of chitosan is 90%. The dispersant is a polyether-modified silane coupling agent with a molecular weight of 1500. The organoboron crosslinking agent is trimethyl borate; The system simulates formation water and particle-based formation water with the same salinity of 10000 mg / L and Na. + Concentration of 9500 mg / L, Ca 2+ Concentration of 300 mg / L, Mg 2+ The concentration is 200 mg / L.
[0032] A method for preparing a slow-expansion gel particle modulating system includes the following steps: S1. Pretreatment of core gel particles: The core gel particles were placed in a vacuum drying oven and dried at 85°C for 3 hours until the moisture content dropped to 0.3%. They were then cooled to room temperature for later use. S2. Preparation of composite coating solution: Sodium alginate and chitosan were added to the granular simulated formation water, and the mixture was stirred at 1800 r / min for 45 min in a 50°C constant temperature water bath. Trimethyl borate and a polyether-modified silane coupling agent with a molecular weight of 1500 were added, and the mixture was stirred for another 25 min. The pH of the reaction system was adjusted to 7.0, and the mixture was then dispersed by ultrasonic waves at 300W for 15 min to prepare a composite coating solution. S3, Coating reaction: The core gel particles pretreated in step S1 were added to the composite coating solution obtained in step S2. The mixture was stirred at 600 r / min and reacted at a constant temperature of 50°C for 1.5 h. The particle size was monitored every 10 min using a laser particle size analyzer, and the coating layer thickness was controlled at 20 nm. S4. Curing and drying: The mixture obtained in step S3 was dried at a constant temperature of 65°C for 5 hours, and then sieved to obtain slow-expanding gel particles with a particle size of 120nm~170nm (hardness 0.9MPa). S5, System Combination: The slow-expansion gel particles with a particle size of 120nm~170nm obtained in step S4 were added to the system to simulate formation water and stirred at 400r / min for 15min to prepare a slow-expansion gel particle regulation and displacement system.
[0033] The performance of the slow-expansion gel particle modulated displacement system prepared in Example 1 was tested: I. Swelling rate test: Under the conditions of 70℃ and mineralization of 10000mg / L, the uncoated gel particles had a swelling rate of 75% after 12 hours and 98% after 24 hours. In this example, the slow-swelling gel particles had a swelling rate of 28% after 12 hours, 45% after 24 hours, and 97% after 72 hours, with a swelling rate reduction of 62.5%. The initial particle size and particle size after swelling time of the slow-swelling gel particle displacement system are shown in the figure. Figure 1 ; The pressure curves during the displacement process of the slow-expansion gel particle displacement system and the uncoated gel particle displacement system (obtained using steps S1, S4, and S5 of this invention) are shown below. Figure 2 ; II. Coating stability test: After standing at 70℃ for 720 hours, the coating remained intact with a peeling rate of 3% and an expansion retention rate of 95%. III. Plugging performance test: At 70℃ and a permeability of 2000mD, the plugging rate was 91.5% and the breakthrough pressure was 0.87MPa; IV. Oil displacement effect test: At 70℃ and a permeability of 2000mD, the waterflood recovery rate was 33.6%. After injecting a 0.5 times pore volume modulated displacement system, the total recovery rate was 44.9%, an increase of 11.3%. V. Temperature and salt resistance test: After standing at 90℃ and 20000mg / L for 720h, there was no stratification or precipitation, the particle shedding rate was 5%, and the expansion rate retention rate was 92%.
[0034] Example 2
[0035] A slow-expansion gel particle modulating system, wherein the modulating system comprises the following components and the mass percentage of each component: Slow-expanding gel particles: 0.1%; Amide-based imidazoline corrosion inhibitor 0.1%; The system simulates the remaining formation water; The components and their mass percentages in the slow-expanding gel particles are as follows: Core gel particles account for 80%; Composite coating material 5%; Dispersant 2%; 0.5% organoboron crosslinking agent; Particles simulate the remaining formation water.
[0036] The mass ratio of partially hydrolyzed polyacrylamide, N,N'-methylenebisacrylamide and urea in the core gel particles is 100:0.5:1, the molecular weight of the partially hydrolyzed polyacrylamide is 10 million, and the particle size of the core gel particles is 50nm~100nm. The composite coating material is composed of sodium alginate and chitosan in a mass ratio of 3:1, wherein the viscosity of sodium alginate is 150 mPa·s and the degree of deacetylation of chitosan is 88%. The dispersant is a polyether-modified silane coupling agent with a molecular weight of 1000; The organoboron crosslinking agent is triethyl borate; The system simulates formation water and particle-based formation water with the same salinity of 15000 mg / L and Na. + Concentration of 13500 mg / L, Ca 2+ Concentration of 1000 mg / L, Mg 2+ The concentration is 500 mg / L.
[0037] A method for preparing a slow-expansion gel particle modulating system includes the following steps: S1. Pretreatment of core gel particles: The core gel particles were placed in a vacuum drying oven and dried at 100°C for 2 hours until the moisture content dropped to 0.2%. They were then cooled to room temperature for later use. S2. Preparation of composite coating solution: Sodium alginate and chitosan were added to the granular simulated formation water, and the mixture was stirred at 2000 r / min for 30 min in a constant temperature water bath at 60℃. Triethyl borate and a polyether-modified silane coupling agent with a molecular weight of 1000 were added, and the mixture was stirred for another 20 min. The pH was adjusted to 7.5, and the mixture was dispersed by ultrasonic waves at 400W for 12 min to prepare a composite coating solution. S3, Coating reaction: The core gel particles pretreated in step S1 were added to the composite coating solution obtained in step S2. The mixture was stirred at 800 r / min and reacted at 60℃ for 1 h. The particle size was monitored every 10 min using a laser particle size analyzer, and the coating layer thickness was controlled at 20 nm. S4. Curing and drying: The mixture obtained in step S3 was dried at 80°C for 4 hours and then sieved to obtain slow-expanding gel particles with a particle size of 70nm~120nm (hardness 1.0MPa). S5, System Combination: The slow-expansion gel particles obtained in step S4 and the amide-imidazoline corrosion inhibitor were added to the simulated formation water in the system and stirred at 500 r / min for 10 min to prepare the slow-expansion gel particle regulation and displacement system.
[0038] The performance of the slow-expansion gel particle modulated displacement system prepared in Example 2 was tested: I. Swelling rate test: Under the conditions of 90℃ and mineralization of 15000mg / L, the uncoated gel particles had a swelling rate of 82% after 12 hours and 99% after 20 hours. In this example, the slow-swelling gel particles had a swelling rate of 22% after 12 hours, 38% after 24 hours, and 98% after 96 hours, with a swelling rate reduction of 79.2%. II. Coating stability test: After standing at 90℃ for 720 hours, the coating remained intact with a peeling rate of 4% and an expansion retention rate of 90%. III. Plugging Performance Test: Artificial core with a permeability of 2000mD, plugging rate of 88.7%, breakthrough pressure of 0.79MPa; IV. Oil displacement effect test: Under the conditions of 90℃ and permeability of 2000mD, the water flooding recovery rate was 32.8%. After injecting a 0.5 times pore volume modulated flooding system, the total recovery rate was 43.4%, an increase of 10.6%. V. Temperature and salt resistance test: After standing at 90℃ and 15000mg / L for 720h, there was no stratification or precipitation, the particle shedding rate was 7%, and the expansion rate retention rate was 88%.
[0039] Example 3
[0040] A slow-expansion gel particle modulating system, wherein the modulating system comprises the following components and the mass percentage of each component: Slow-expanding gel particles: 0.5%; Phosphate imidazoline corrosion inhibitor 0.5%; The system simulates the remaining formation water; The components and their mass percentages in the slow-expanding gel particles are as follows: Core gel particles: 60%; Composite coating material 15%; Dispersant 5%; 2% organic boron crosslinking agent; Particles simulate the remaining formation water.
[0041] The core gel particles contain partially hydrolyzed polyacrylamide, N,N'-methylenebisacrylamide, and urea in a mass ratio of 100:2:3. The partially hydrolyzed polyacrylamide has a molecular weight of 15 million, and the core gel particles have a particle size of 150 nm to 200 nm. The composite coating material is composed of sodium alginate and chitosan in a mass ratio of 2.5:1, wherein the viscosity of sodium alginate is 250 mPa·s and the degree of deacetylation of chitosan is 92%. The dispersant is a polyether-modified silane coupling agent with a molecular weight of 2000; The organoboron crosslinking agent is sodium borohydride; The system simulates formation water and particle-based formation water with the same salinity of 5000 mg / L and Na. + Concentration of 3000 mg / L, Ca 2+ Concentration of 800 mg / L, Mg 2+ The concentration is 500 mg / L.
[0042] A method for preparing a slow-expansion gel particle modulating system includes the following steps: S1. Pretreatment of core gel particles: The core gel particles were placed in a vacuum drying oven and dried at 80°C for 4 hours until the moisture content dropped to 0.4%. They were then cooled to room temperature for later use. S2. Preparation of composite coating solution: Sodium alginate and chitosan were added to the granular simulated formation water, and the mixture was stirred at 1500 r / min for 60 min in a constant temperature water bath at 40℃. Sodium borohydride and a polyether-modified silane coupling agent with a molecular weight of 2000 were added, and the mixture was stirred for another 30 min. The pH of the reaction system was adjusted to 6.5, and the mixture was dispersed by ultrasonic waves at 200W for 18 min to prepare a composite coating solution. S3, Coating reaction: The core gel particles pretreated in step S1 were added to the composite coating solution obtained in step S2. The mixture was stirred at 500 r / min and reacted at 40°C for 2 h. The particle size was monitored every 10 min using a laser particle size analyzer, and the coating layer thickness was controlled at 25 nm. S4. Curing and drying: The mixture obtained in step S3 was dried at a constant temperature of 60°C for 6 hours, and then sieved to obtain slow-expanding gel particles with a particle size of 175nm~225nm (hardness 0.85MPa). S5, System Combination: The slow-expansion gel particles obtained in step S4 and the phosphate imidazoline corrosion inhibitor were added to the simulated formation water in the system and stirred at 300 r / min for 20 min to prepare the regulation and displacement system.
[0043] The performance of the slow-expansion gel particle modulated displacement system prepared in Example 3 was tested: I. Swelling rate test: Under the conditions of 90℃ and mineralization of 5000mg / L, the uncoated gel particles had a swelling rate of 70% after 12 hours and 97% after 22 hours. In this example, the slow-swelling gel particles had a swelling rate of 20% after 12 hours, 35% after 24 hours, and 96% after 84 hours, with a swelling rate reduction of 72.7%. II. Coating stability test: After standing at 90℃ for 720 hours, the coating remained intact with a peeling rate of 2% and an expansion retention rate of 96%. III. Plugging Performance Test: 90℃, 1000mD permeability artificial core, 95.6% plugging rate, breakthrough pressure 1.12MPa; IV. Oil displacement effect test: Under the conditions of 90℃ and permeability of 1000mD, the water flooding recovery rate was 32.2%. After injecting a 0.5 times pore volume modulated flooding system, the total recovery rate was 45.7%, an increase of 13.8%. In this embodiment, the injection pressure, water cut, and recovery rate curves of the slow-expansion gel particle controlled-flood system during the controlled-flood experiment are shown in the figure. Figure 3 ; V. Temperature and salt resistance test: After standing at 110℃ and 3000mg / L for 720h, there was no stratification or precipitation, the particle shedding rate was 3%, and the expansion rate retention rate was 95%.
[0044] This invention effectively reduces the swelling rate of gel particles: the core-shell structure formed by the sodium alginate-chitosan composite coating material slows down the penetration rate of water into the core particles (reducing the penetration rate by 60%~75%), thus reducing the swelling rate of the gel particles by 60%~92% (existing uncoated gel particles reach their maximum swelling rate within 12h~24h, while the slow-swelling gel particles of this invention reach their maximum swelling rate within 60h~108h); specific data shows that under conditions of 75℃ and a mineralization of 10000mg / L, the uncoated particles... The expansion rate reaches 75% in 12 hours and 98% in 24 hours. The expansion rate of the slow-expanding gel particles of this invention is only 28% in 12 hours, 45% in 24 hours, and 97% in 72 hours. This avoids the particles from rapidly swelling and clogging in the near-wellbore area, ensuring that the modulated drive system can smoothly migrate to the deep reservoir (the migration distance is increased by 40%~60% compared with the existing system), and expanding the modulated drive coverage. The slow hydrolysis characteristics of the composite coating material (hydrolysis rate 0.02g / h~0.05g / h) can achieve precise control of the swelling rate, adapting to the needs of reservoirs with different permeability.
[0045] This invention balances the effects of slowed expansion and plugging performance: the composite coating material only slows down the swelling rate without affecting the final expansion ratio of the core particles (still maintaining 8 to 35 times) and the plugging strength, achieving a plugging rate of 86% to 95%. Core plugging experiments show that for artificial cores with a permeability of 2000 mD, the plugging rate reaches 93% after injecting the system of this invention, effectively plugging high-permeability channels in the reservoir and forcing the injected fluid to shift to low-permeability areas. The coating layer is firmly bonded to the core particles (720h detachment rate ≤ 5%), and is not easily detached under high temperature, high salinity, and shearing conditions, extending the effective period of the system to 15 to 20 months. The modified flood control system of this invention exhibits excellent temperature and salt resistance: the composite coating material and the core gel particles work synergistically, ensuring that the modified flood control system remains stratified and free of sedimentation after 720 hours of standing in reservoir environments with temperatures ranging from 50℃ to 130℃ and salinity from 3000 mg / L to 55000 mg / L. The gel particle shedding rate is ≤8%, and the expansion rate retention rate is ≥88%. Even at 120℃ and a salinity of 50000 mg / L, the expansion rate retention rate still reaches 90%, making it suitable for the modified flood control needs of various complex reservoirs and solving the problem of poor stability of existing slow-expansion systems in high-temperature and high-salt environments (the existing system has an expansion rate retention rate of only 60% to 70% after 72 hours). The preparation process of the modified flow system of this invention is simple and cost-controllable: the preparation method does not require complex equipment, and conventional chemical equipment can be used to achieve large-scale production with a production efficiency of 500 kg / d; the composite coating materials (sodium alginate and chitosan) are widely available and inexpensive (sodium alginate is priced at approximately RMB 15-20 / kg, and chitosan at approximately RMB 30-40 / kg), and the amount used is small. Compared with existing modified flow systems, the preparation cost is reduced by 10%-18%; at the same time, the addition of corrosion inhibitors (corrosion inhibition rate ≥90%) can reduce corrosion of injection and production equipment (corrosion rate ≤0.05 mm / a), thereby reducing construction costs and equipment maintenance expenses; The modified flow system of this invention is environmentally friendly and does not damage the reservoir: the composite coating materials (sodium alginate and chitosan) are all environmentally friendly and biodegradable materials (biodegradation rate ≥80%), which will not cause pollution to the reservoir and the environment; the modified flow system has good compatibility with reservoir rocks (contact angle ≤45°), will not cause secondary blockage (core permeability damage rate ≤5%), and does not damage the reservoir, and can be widely used in green modified flow exploitation of various oil reservoirs.
[0046] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A slow-expansion gel particle modulating system, characterized in that: The components and their mass percentages in the controlled-drive system are as follows: Slow-expanding gel particles: 0.1%~0.5%; Corrosion inhibitor 0.05%~0.8%; The system simulates the remaining formation water; The components and their mass percentages in the slow-expanding gel particles are as follows: Core gel particles: 55%~85%; Composite coating material 4%~18%; Dispersant 1%~6%; Organic boron crosslinking agent 0.3%~2.5%; Particles simulate the remaining formation water.
2. The slow-expansion gel particle modulating system according to claim 1, characterized in that: The core gel particles are acrylamide-based gel particles; the particle size of the core gel particles is 50nm~200nm, and the expansion ratio is 8 to 35 times; the components of the acrylamide-based gel particles include partially hydrolyzed polyacrylamide, crosslinking agent, and stabilizer, with a mass ratio of partially hydrolyzed polyacrylamide, crosslinking agent, and stabilizer of 100:(0.3~2.5):(0.8~3.5); the molecular weight of the partially hydrolyzed polyacrylamide is 8 million to 20 million; the crosslinking agent is N,N'-methylenebisacrylamide; and the stabilizer is urea.
3. The slow-expansion gel particle modulating system according to claim 1, characterized in that: The composite coating material comprises sodium alginate and chitosan, with a mass ratio of sodium alginate to chitosan of (1.8~3.2):1; the viscosity of sodium alginate is 100mPa·s~300mPa·s; and the degree of deacetylation of chitosan is ≥85%.
4. The slow-expansion gel particle modulating system according to claim 1, characterized in that: The dispersant is a polyether-modified silane coupling agent with a molecular weight of 800-2200.
5. The slow-expansion gel particle modulating system according to claim 1, characterized in that: The organoboron crosslinking agent is at least one of trimethyl borate, triethyl borate, or sodium borohydride.
6. The slow-expansion gel particle modulating system according to claim 1, characterized in that: The corrosion inhibitor is an imidazoline corrosion inhibitor; the imidazoline corrosion inhibitor is at least one of alkyl imidazoline corrosion inhibitor, amide imidazoline corrosion inhibitor, or phosphate imidazoline corrosion inhibitor.
7. The slow-expansion gel particle modulating system according to claim 1, characterized in that: The simulated formation water and particle-based simulated formation water in the system are simulated formation water with identical compositions. The salinity of the simulated formation water is 3000 mg / L to 55000 mg / L, and the Na+ content in the simulated formation water is... + Concentrations of 1000 mg / L to 30000 mg / L, Ca 2+ Concentrations of 100 mg / L to 2000 mg / L, Mg 2+ The concentration ranges from 100 mg / L to 2000 mg / L.
8. A method for preparing the slow-expansion gel particle modulating system according to any one of claims 1 to 7, characterized in that: Includes the following steps: S1. Vacuum dry the core gel particles at 75℃~105℃ for 1.5~4.5h, and cool them to room temperature for later use. S2. Add sodium alginate and chitosan to the granular simulated formation water, and stir at 1200r / min to 2200r / min for 25min to 65min at 35℃ to 65℃. Then add organoboron crosslinking agent and dispersant, and continue stirring for 15min to 35min. Adjust the pH of the reaction system to 6.0 to 8.0 to prepare a composite coating solution. S3. Add the core gel particles processed in step S1 to the composite coating solution obtained in step S2, and react at a constant temperature of 35℃~65℃ for 0.8h~2.5h with stirring at a speed of 400r / min~900r / min to form core-shell structured slow-expansion gel particles. S4. The mixture obtained in step S3 is dried at 55℃~85℃ for 3.5h~6.5h, and then the slow-expansion gel particles with a particle size of 70nm~240nm are screened out. S5. Add the slow-expansion gel particles with a particle size of 70nm~240nm selected in step S4 and the corrosion inhibitor to the simulated formation water in the system, and stir at a speed of 250r / min~550r / min for 8min~25min to obtain the slow-expansion gel particle regulation and driving system.
9. The method for preparing the slow-expansion gel particle modulating system according to claim 8, characterized in that: In step S2, the stirring process is supplemented by ultrasonic dispersion with a power of 150W~550W for 10min~20min. In step S3, the constant temperature reaction is monitored in real time by a laser particle size analyzer, and the data is recorded every 10min to ensure that the coating layer thickness is uniform, and the coating layer thickness is 20nm~40nm.
10. The application of the slow-expansion gel particle modulating and flooding system according to any one of claims 1 to 7 in modulating and flooding production of high, medium, and low permeability reservoirs, high-temperature and high-salinity reservoirs, and heterogeneous reservoirs, characterized in that: The permeability of the high, medium and low permeability reservoirs is 50mD~2000mD; the temperature of the high temperature and high salinity reservoirs is 50℃~130℃ and the salinity is 3000mg / L~55000mg / L; the coefficient of variation of permeability of the heterogeneous reservoirs is 0.5~1.2.